Role of the Clinical Pharmacist in Reducing Preventable Adverse Drug Events - A.Mshiemish, Bahir (Iraqi Journal of Pharmaceutical Sciences, 2017)
According to so many previous studies, lack of sufficient information during prescribing steps may lead to medication errors. Thus, the presence of the clinical pharmacist during routine rounding process in the ward with intervention of patient care plan may reduce the probability of adverse drug events (ADEs).This study evaluate role of the clinical pharmacists, as a member of medical team with the physician, on ADEs and report their interventions in the internal medicine unit. This study was designed to compare between two groups of patients, those receiving care from a rounding team (physician, nurse, and clinical pharmacist) (study or intervention group with 51 patient); and those receiving care from a rounding team (physician and nurse, but without any pharmacist) (control group with 49 patient). The primary outcome measure was preventable ADEs and secondary one involves the time of staying in the hospital and onset of response to therapy. Patients were randomly selected, followed a single-blind design, and evaluated by a senior physicians and clinical pharmacists who document their medical interventions.Specialist physicians accepted (60) of (77) recommendations (i.e. do modifications in drug therapy depending on clinical pharmacist interventions). The most common intervention was recommending dosage or frequency of medication (32.4%), followed by addition of medication (19.5%).The rate of preventable ordering ADEs in the study unit was 77% lower than in the control unit (P<0.05). There was no significant difference (p>0.05) in the cost of drug therapy between patient groups. Patients with ADEs in the control group had an average of 1.5 day longer staying period at the hospital; which was not differ significantly (p>0.05) from the study group.In summary, presence of clinical pharmacist during tour as a full member of the patient care team in internal medicine ward was associated with a substantially lowered rate of ADEs which caused by prescribing errors. Types of errors indicate the need for activation of the clinical pharmacist's interventions.Key words: adverse drug events (ADEs), clinical pharmacist.